Role-Play as an Effective Way to Teach Relationship Building with Telehealth - Lynn McIvor; Michele Karnes (Scholarworks @ WMU, 2019)
Telehealth has been described in the literature as an emerging niche for occupational therapists. The profession needs to move toward cost-effective and efficient ways to provide services while not adding to the increasing cost of health care, and one way of doing this is through telehealth. The research supports the importance of the therapeutic relationship, and that telehealth changes how we develop this bond; however, the literature does not provide educators with information on how to teach this to students. The purpose of this article is to highlight the potential of using role-play to educate students on how to develop a therapeutic relationship while using telehealth. This project included a course that was presented over three modules to teach the skills needed for developing relationships while using telehealth. A pre and postsurvey design was used to measure if there were changes in the students' perceptions of their abilities to establish relationships while using telehealth. Sixteen students participated. After completing the three modules, the students improved their confidence in their abilities to develop a therapeutic relationship and felt that role-play was effective for teaching these skills. It is important to provide students with opportunities to role play while using telehealth as a part of their coursework.